High carrier mobility tungsten-doped indium oxide films prepared by reactive plasma deposition in pure argon and post annealing. (February 2022) - Gan, Tian; Li, Jingmei; Wu, Lili; Zhang, Jingquan; Hao, Xia; Zhang, Qingyuan; Li, Ruixing; Shi, Wenhui
Abstract: Tungsten-doped indium oxide films were deposited by reactive plasma deposition using a low doped target in pure argon atmosphere at room temperature. Post thermal annealing was conducted in different atmospheres in the range of 150 °C–250 °C to improve the properties of films. The structural, electrical and optical properties of IWO films with different annealing conditions have been investigated. It is found that crystallization after annealing is an effective way to improve the mobility. The mobility of the polycrystalline films is much greater than amorphous films. And the ordered structure is conducive to interstitial oxygen and oxygen in the atmosphere to fill the oxygen vacancies, leading to the decrease of the carrier concentration and a further increase of the mobility. We have prepared IWO thin films with the carrier mobility (up to 83 cm 2 V −1 s −1 ), even if as-deposited films had a relatively low carrier mobility (∼30 cm 2 V −1 s −1 ). The optical transmittance of IWO films maintains 89% and 84% in visible and near-infrared regions, respectively. The mobility of IWO films is found to depend on the manufacture of the source target and the highest mobility of 120 cm 2 V −1 s −1 has been reached.